Altered Expression of EPO Might Underlie Hepatic Hemangiomas in LRRK2 Knockout Mice. (30th October 2016) - Wu, Ben; Xiao, Kaifu; Zhang, Zhuohua; Ma, Long
Abstract : Parkinson's disease (PD) is a severe neurodegenerative disorder caused by progressive loss of dopaminergic neurons in the substantia nigra pars compacta of the midbrain. The molecular mechanism of PD pathogenesis is unclear. Mutations in the leucine-rich repeat kinase 2 ( LRRK2 ) gene are a common genetic cause of familial and sporadic PD. However, studies on LRRK2 mutant mice revealed no visible dopaminergic neuronal loss in the midbrain. While surveying a LRRK2 knockout mouse strain, we found that old animals developed age-dependent hepatic vascular growths similar to cavernous hemangiomas. In livers of these hemangioma-positive LRRK2 knockout mice, we detected an increased expression of the HIF-2 α protein and significant reactivation of the expression of the HIF-2 α target gene erythropoietin ( EPO ), a finding consistent with a role of the HIF-2 α pathway in blood vessel vascularization. We also found that the kidney EPO expression was reduced to 20% of the wild-type level in 18-month-old LRRK2 knockout mice. Unexpectedly, this reduction was restored to wild-type levels when the knockout mice were 22 months to 23 months old, implying a feedback mechanism regulating kidney EPO expression. Our findings reveal a novel function of LRRK2 in regulating EPO expression and imply a potentially novel relationship between PD genes and hematopoiesis.